Part X – October 1968 - Papers - The Magnesium-Titanium Phase Diagram to 1.0 pct - L. C. Fincher; D. H. Desy (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1969)
The magnesium-rich end of the Mg-Ti phase diagram was investigated. The liquidus, solidus, and solvus boundaries to 1 pct Ti were established. All alloys were prepared by saturating molten magnesium with titanium in a consumable titanium crucible under inert gas maintained at 230 psig. The liquidus of the Mg- Ti system was determined by analysis of dip samples taken from 700° to 1300°C under equilibrium conditions in a pressurized inert atmosphere furnace and by analysis of small ingots rapidly poured and quenched from 1400° to 1500°C. The solubility of titanium in magnesium ranged from 0.018 wt pet Ti at 700°C (0.012 wt pet at 650°C by extrapolation) to 1.035 wt pet Ti at 1500°C. The solidus for compositions ranging from 0.03 to 1.00 wt pet Ti was determined to be 650° ± 1°C by thermal analysis. The titanium solid solubility values ranged from 0.08 wt pet at 350°C to 0.19 wt pet by extrapolation to 650°C. The freezing reaction is peritectic. No intermetallic compounds were found in the system; the phase in equilibrium with molten magnesium saturated with titanium was found to be titanium with magnesium in solid solution. Solid titanium will dissolve at least 1.32 wt pct Mg. PREVIOUS investigations of the Mg-Ti system have shown considerable disagreement on the solubility of titanium in liquid magnesium. Furthermore, the solid solubility of titanium in magnesium has not been well established. Liquidus curves for previous work and for the present investigation are shown in Fig. 1. Aust and Pidgeon1 used a dip-sampling method on molten magnesium held in equilibrium with solid titanium under a protective atmosphere to determine the solubility and found that it ranged from 0.0025 wt pet Ti at 651°C to 0.015 wt pet Ti at 850°C. Eisenreich2 introduced titanium into molten magnesium by means of TiCL4 adsorbed on BaCl2. Ingots were then cast at various temperatures. Making the assumption that only the titanium dissolved in magnesium at the time of casting was soluble in H2SO4, Eisenreich determined the solubility of titanium in molten magnesium to range from 0.003 wt pet at 655°C to 0.115 wt pet at 800°C. Eisenreich also determined the solid solubility of titanium in magnesium to be 0.015 wt pet at room temperature and 0.045 wt pet at 500°C. Since the solid solubility just below the freezing temperature for the bulk of the alloy was much larger than the liquid solubility just above the freezing temperature, Eisenreich concluded that the freezing reaction was peritectic. Obinata et al.3 equilibrated molten magnesium with titanium in hermetically sealed titanium containers which were then furnace-cooled. The titanium content of the magnesium was then determined and found to range from 0.170 wt pet at 700°C to 0.85 wt pet at 1200°C. No intermetallic compound was found in the system. The Armour Research Foundation4 determined two points on the solvus by electrical resistivity methods: 0.00057 wt pet at 200°C and 0.0008 wt pet at 300°C. At higher temperatures, data were meaningless with no trends observable. The authors of this report believed that the lack of significant data at the higher temperatures was due to variations in specimen geometry, although there was no positive evidence to verify this supposition. The present investigation was undertaken to clarify the uncertainty in both the liquidus and solvus of the magnesium-rich end of the Mg-Ti system. EQUIPMENT AND MATERIALS The equipment used in this investigation, with some modifications, was essentially that used by Crosby and Fowler5 in their determination of part of the Mg-Zr phase diagram. The equipment, as modified for this work, is shown in Fig. 2. It consists of a sealed furnace chamber which can be pressurized with inert gas so that melts can be made above the boiling point of magnesium at atmospheric pressure. Melts are made by induction heating in a titanium crucible which, after diffusion of sufficient magnesium into the walls of the crucible to saturate the titanium at the sampling temperature, comprises the solid phase in equilibrium with the molten magnesium. Dip samples may be taken with the sampling tube, or the entire furnace may be tilted so that ingots may be poured into a mold in the side chamber. The principal difference from the earlier apparatus is in the thermocouple, which in the present equipment is enclosed in a protection tube and immersed directly in the melt. The tips of both the thermocouple protection tube and the sampling tube, which dip into the melt, are made of high-purity titanium. The 4 1/2-in.-long titanium tip of the sampling tube is threaded into a steel tube, O in Fig. 2, which extends through the top of the furnace. To determine whether the temperature at the tip of